The Juridical Analysis of the Legal Consequences of Granting Land Rights Without the Consent of Heirs and the Liability of Notaries & PPAT - Sutan Dio Dwiky Purnomo; Aziza Kamila Zakaria; Daffa Khoiri; Dedi Pranata (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This research analyzes the legal consequences of granting land rights without the consent of other heirs and examines the legal responsibility of Notaries and/or Land Deed Officials (Pejabat Pembuat Akta Tanah/PPAT) in the preparation of such grant deeds. In practice, land grants are frequently executed without due consideration of the absolute rights (legitime portie) of lawful heirs, resulting in inheritance disputes and legal uncertainty regarding the validity of the grant and subsequent land registration. This study employs normative legal research using a statutory approach and a conceptual approach. The analysis is based on primary legal materials in the form of legislation regulating grants, inheritance law, land registration, and notarial authority, supported by secondary legal materials including legal doctrines, scholarly journals, and relevant legal opinions. The findings demonstrate that a land grant made without the consent or acknowledgment of other heirs may be subject to legal challenge and potential annulment, particularly when it infringes upon the legitime portie guaranteed by the Indonesian Civil Code. Furthermore, the study reveals that Notaries/PPAT bear professional and legal obligations to apply the principle of prudence, verify the legal status of the parties, and ensure compliance with applicable laws. Failure to fulfill these obligations may result in administrative sanctions, civil liability for damages, and, in certain circumstances, criminal responsibility. However, the liability of Notaries/PPAT may be excluded if it can be proven that the deed was prepared in good faith and that any defects arose from falsified data or the concealment of material facts by the parties. This research contributes to the development of inheritance and notarial law by providing a clearer framework for assessing the validity of land grants and reinforcing the role of Notaries/PPAT in ensuring legal certainty, justice, and protection for all interested parties.